A mixed methods examination of adolescents' reasons for pretending to text. (19th October 2018) - Tulane, Sarah; Vaterlaus, J. Mitchell; Beckert, Troy E.
ABSTRACT: Introduction: The purpose of this study was to examine reasons adolescents give for pretending to text in various social situations. Pretending to text was conceptualized as when a person uses a cellphone to make it look like they are texting, but they are not actually sending messages. Little research is available from the adolescent perspective regarding self‐presentation and avoidance when using digital devices in social contexts. Methods: A convergent mixed methods approach was used to understand the experience of high school sophomores, juniors, and seniors ( n = 216) in the United States. Chi‐square analyses and t‐ tests were used to examine differences between those who pretended to text and those who did not. Qualitative data were analyzed using van Manen's line‐by‐line approach. Results & conclusions: Participants indicated they pretended to text for reasons of avoidance, to maintain a positive appearance, and sometimes to provide a sense of security if they felt unsafe in a situation. This study uses self‐presentation to further understand adolescent perceptions of pretending to text.